2019
DOI: 10.33549/physiolres.933950
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric activation of yeast enzyme neutral trehalase by calcium and 14-3-3 protein

Abstract: Neutral trehalase 1 (Nth1) from Saccharomyces cerevisiae catalyzes disaccharide trehalose hydrolysis and helps yeast to survive adverse conditions, such as heat shock, starvation or oxidative stress. 14-3-3 proteins, master regulators of hundreds of partner proteins, participate in many key cellular processes. Nth1 is activated by phosphorylation followed by 14-3-3 protein (Bmh) binding. The activation mechanism is also potentiated by Ca(2+) binding within the EF-hand-like motif. This review summarizes the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 104 publications
1
3
0
Order By: Relevance
“…The 13 residues (Pro 149 -Val 161 ) connecting both motifs and the last two residues (Asn 167 and Lys 168 ) were not visible in the electron density, likely due to their flexibility. Both pSer 139 and pSer 164 moieties are coordinated, as expected, by the side chains of 14-3-3c residues Lys 50 , Arg 57 , Arg 132 , and Tyr 133 , in agreement with previously published structures of 14-3-3 complexes [20,[31][32][33][34][35][36]. The comparison with the previously reported structure of an isolated pSer 164 motif bound to 14-3-3c [20] revealed similar but not identical mainchain conformation and interactions with 14-3-3c ( Figs 6C and 7A,C).…”
Section: Crystal Structure Of the 14-3-3:proc2 Ps139+ps164 Complexsupporting
confidence: 92%
“…The 13 residues (Pro 149 -Val 161 ) connecting both motifs and the last two residues (Asn 167 and Lys 168 ) were not visible in the electron density, likely due to their flexibility. Both pSer 139 and pSer 164 moieties are coordinated, as expected, by the side chains of 14-3-3c residues Lys 50 , Arg 57 , Arg 132 , and Tyr 133 , in agreement with previously published structures of 14-3-3 complexes [20,[31][32][33][34][35][36]. The comparison with the previously reported structure of an isolated pSer 164 motif bound to 14-3-3c [20] revealed similar but not identical mainchain conformation and interactions with 14-3-3c ( Figs 6C and 7A,C).…”
Section: Crystal Structure Of the 14-3-3:proc2 Ps139+ps164 Complexsupporting
confidence: 92%
“…In addition, PKA sites S20 and S21 regulate the dephosphorylation of Nth1 at the downstream Bmh1 site. Residues D478 and E674 serve as catalytic acids and bases, respectively, and the entire process is enhanced in the presence of Ca 2+ [72,73]. Therefore, the binding of Nth1 to 14-3-3 triggers the activity of Nth1 by stabilizing the three-dimensional structure of the catalytic domain and calcium-binding domain of Nth1, thereby stabilizing the active site required for catalysis.…”
Section: Gh37 Trehalasementioning
confidence: 99%
“…Metal ions may have a bidirectional effect on trehalases. Alblova et al demonstrated that the presence of Ca 2+ could enhance the activation of Nth1 of GH37 family [73]. Acidic trehalases remain unaffected by divalent cations.…”
Section: Effect Of Metal Ionsmentioning
confidence: 99%
“…Here, we focus on the regulation of the final step in the trehalose pathway, the trehalase Nth1, which converts trehalose back to glucose (21). Nth1 has been extensively studied as a model for metabolic regulation because it has both an interesting regulatory mechanism and is experimentally well accessible (22) . We and others have shown that the catalytic activity of Nth1 is determined by both the cell cycle kinase CDK (cyclin dependent kinase) (16,19) and the metabolic kinase PKA (protein kinase A) (23,24).…”
Section: Introductionmentioning
confidence: 99%